ESTIMASI TINGKAT PENGEMBALIAN SAHAM SEKTOR MANUFAKTUR YANG TERCATAT DI BURSA EFEK INDONESIA - Warsono, Warsono (Faculty of Economics and Business, University of Muhammadiyah Malang, 2010)
This study aims to find out and at the same time test empirically whether financial performance can be used as an estimator of the stock returns of listed manufacturing sector in Indonesia Stock Exchange. Data analysis tool used is ordinary least square regression (OLS). Based on data analysis using SPSS program version 15 obtained the conclusion that fundamental analysis, with explanatory variables of financial performance, can not be used as an estimator of the stock returns of manufacturing sector. This means that this research hypothesis was rejected. Thus, investors should not need to consider the financial performance at a particular time in making their investment decisions.